Growth and proline content in pigeon pea seedlings subjected to osmotic stress and to exogenous putrescine - Monteiro, Juliana Geseíra; Rodrigues Cruz, Flávio José; Nardin, Mariana Batista; Santos, Durvalina Maria Mathias dos (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to verify the effect of the application of the polyamine putrescine on the accumulation of proline and on the early seedling growth of pigeon pea subjected to water or salt stress, and to evaluate whether this polyamine can be used to alleviate these stresses. Seeds of two cultivars of pigeon pea, BRS Mandarim and Caqui, were germinated in gerbox boxes lined with filter papers soaked with 0.0, -0.2, -0.3, -0.4, -0.5 MPa PEG 6000 or 0, 20, 40, 60, 80, and 120 mmol L-1 NaCl, in the absence (0 mmol L-1) or presence (0.5 mmol L-1) of putrescine. A completely randomized design was used, in a 2x5x2 and 2x6x2 factorial arrangement (two cultivars, five levels of drought or six levels of salt stress, and presence or absence of putrescine), with four replicates. Seedling growth is highly reduced by water restriction and salinity conditions. Exogenous putrescine increases, under both stresses, the proline contents in pigeon pea seedlings, especially in the cultivar BRS Mandarin, and alleviates the effects of moderate water deficiency on the studied cultivars. Water restriction and salinity stresses cause accumulation of proline content in shoots and roots of both cultivars. Proline can be considered a good biochemical and physiological indicator of these stresses in pigeon pea seedlings.